Measuring Fatigue in Multiple Sclerosis: A Rapid Review - Namsrai, Tergel; Parkinson, Anne; Burns, Richard; Herkes, Geoffrey; Elisha, Mark; Chisholm, Katrina; Drew, Janet; Fanning, Vanessa; Brüstle, Anne; Suominen, Hanna; Cherbuin, Nicolas; Desborough, Jane (Springer Nature, 2026)
Background
Fatigue is one of the most prevalent and debilitating symptoms of multiple sclerosis (MS), as people with MS describe it. It has a complex pathogenesis and often precedes the clinical symptoms of MS and potentially indicates disease progression. Given its prevalence, impact, and intricate connections to disease pathology, accurate measurement is crucial to manage and study fatigue in people with MS; however, current measurements often lack content validity. A mismatch between key aspects of fatigue and existing fatigue scales will limit these scales’ ability to capture the full scope of MS-related fatigue. We aimed to examine the current evidence on MS-related fatigue to define key aspects of fatigue in the literature and compare them with the scales used to measure MS-related fatigue.
Methods
This integrated rapid review (PROSPERO registration: CRD42024505743) synthesised evidence on MS-related fatigue domains and their representation in validated scales. A systematic search was conducted on January 24, 2024, across three electronic databases: PubMed, Scopus, and ProQuest with no restriction on publication date. Eligible studies included those reporting on fatigue domains, signs and symptoms in people with MS and those on validated fatigue scales in MS. The quality of the included studies was assessed using the Mixed Methods Assessment Tool. Data was synthesised with meta-aggregation of the fatigue domains, signs, and symptoms and mapping them against the items from validated fatigue scales.
Results
We identified 7089 articles and included 85 studies (quantitative: 65; qualitative: 9; mixed methods: 8); 54 investigated fatigue domains, five reported fatigue scale development, and 26 focused on both. The review included 34,984 participants (9814 male; 25,126 female) with a mean age of 47.43 years (range 36–55.4). A total of 791 items related to fatigue domains, signs, symptoms, and experiences were extracted and categorised into three key areas: fatigue triggers, domains, and impacts. We identified eight fatigue triggers (physical, cognitive, psychological, social, medical, lifestyle, temporal, and environmental), five fatigue domains (general, physical, cognitive, psychosocial, and social), and five areas of fatigue impact (global, physical, cognitive, psychological, and social impacts of fatigue). Twenty-nine scales, tests, measures, and indices that measure MS-related fatigue were identified. Nineteen of these were validated by self-reported fatigue scales. The scales fully covered the domains of MS-related fatigue. However, the identified scales did not fully capture medical and lifestyle triggers, as well as psychological and global impacts. Additionally, no single scale fully encompassed all three aspects of fatigue and their corresponding subcategories.
Conclusion
This review demonstrates the importance of integrating the subjective experiences of people with MS into research to ensure that the multidimensional aspects of MS-related fatigue, together with these people’s values, needs, and preferences, are captured and used to develop useful, comprehensive, and meaningful tools designed to measure MS-related fatigue. In addition, this clearer discernment of the triggers, domains, and impacts of MS-related fatigue is critical in the clinic and research. Better tools will enable a better understanding of the underlying mechanisms, as well as tracking and managing fatigue.